Antioxidant activity of Rafflesia kerrii flower extract - Puttipan R. (2014)
Rafflesia kerrii has been used in Thai traditional remedies for treatment of several diseases. However, scientific data particularly on biological activities of this plant is very rare. The present study explores an antioxidant activity of R. kerrii flower (RKF). Extracting solvent and extraction procedure were found to play an important role on the activity of RKF extract. The extract obtained from water-ethanol system showed higher antioxidant activity than that from water-propylene glycol system. Fractionated extraction using different solvents revealed that methanol fractionated extract (RM) possessed the highest antioxidant activity with Trolox equivalent antioxidant capacity (TEAC) and inhibitory concentration of 50% inhibition (IC50) values of approximately 39 mM/mg and 3 μg/mL, respectively. Phytochemical assays demonstrated that RM contained extremely high quantity of phenolic content with gallic antioxidant equivalent (GAE) and quercetin equivalent (QE) values of approximately 312 mg/g and 16 mg/g, respectively. Ultraviolet-visible spectroscopy (UV-VIS) and high-pressure liquid chromatography (HPLC) indicated that gallic acid was a major component. RM which was stored at 40°C, 75% RH for 4 months showed slightly significant change (p < 0.05) in phytochemical content and antioxidant activity with zero order degradation. The results of this study could be concluded that R. kerrii flower was a promising natural source of strong antioxidant compounds.